Evaluación de seis densidades de siembra y su productividad en el cultivo de chocho (Lupinus mutabilis Sweet) en la parroquia Chugchilán, cantón Sigchos, provincia Cotopaxi 2020. - Narvaez Chuquiano, Maritza Elizabeth (2021)
This research study was carried out in the community of ‘Guayama Grande’, in Chugchilán Parish, on "Evaluation of six sowing densities and their productivity in the cultivation of chocho (Lupinus mutabilis Sweet), in order to determine the optimal sowing density for the community. The objectives of this research study were to determine the optimal sowing density for the cultivation of chocho (Lupinus mutabilis Sweet), to evaluate the effect of sowing densities and their behavior, to analyse the productivity of chocho. In order to carry out the proposed objectives a Randomized Complete Block Design (RCBD) was used with six treatments and three replications, giving a total of eighteen experimental units. The field research was used since the data obtained in the research were during the phenological development of the crop, specifically from the development of the flower bud until the moment of harvesting. The results of the study revealed that the Iniap 450 variety, with the behavior of the six proposed densities, showed that at density 3 (30cm x 4 seeds) its production in kilograms/hectare was 1000Kg/ha: 1tn/ha, followed by a density of 4 (40 cm x 4 seeds) with an average of 900 kg/ha; 0.90 tn/ha, the lowest yielding density is density 5 (distance of 50 cm x 4 seeds) with an average of 180 kg/ha; 0.18 tn/ha. The cost / benefit ratio shows that at a density of 30 cm there are positive values, reaching a cost / benefit ratio of 4.67; where for every dollar invested the profit is $3.67, making it a profitable and acceptable treatment.